PARIS... c’est pas fini! - Maria do Rosário Girão Ribeiro dos Santos (Carnets)
The departure and stay in a foreign country imply a double movement of invasion/evasion grounded in the dichotomy identity/alterity, I/the other, here/there or, more specifically, in the antinomy appropriation/distance. To this respect, Paris, a notoriously mythical space, lends itself to the expectant look of the neophyte that takes refuge there, for reasons of literary apprenticeship leading to the wish of materialising a vocation (the case of París non se acaba nunca by Enrique Vila-Matas), of succeeding individually and socially (El síndrome de Ulises by Santiago Gamboa presents several testimonies respecting the image of the French capital in a given conjuncture) and finding a safe haven for a forced exile (the emigration in France, during Franco’s regime, narrated by Almuneda Grandes in El corazón helado). On the one hand we have dream and the mirage; on the other, hostility and disillusion…